PENDIDIKAN KARAKTER PEDULI LINGKUNGAN BERBASIS AL-QUR’AN: (Analisis Ekoteologi Tafsir Al-Misbah QS. Al-A’raf 56-58) - Ilmaknun, Lulu; Arini, Aida (PGMI UNHASY, 2025)
This study discusses the character education of environmental care based on the interpretation of M. Quraish Shihab on Surah Al-A'raf verse 56-58 in the interpretation of Al-Misbah. Using a qualitative approach and descriptive analysis method with the type of library research (library research). Primary data sourced from the text of Al-Qur'an Surat al-A'raf verse 56-58, Tafsir Al-Misbah, and Book Education for Character by Thomas Lickona and Islamic Ethics: Study of Social and Environmental Ethics by Sukron Kamil. Secondary data in the form of books, articles, and relevant journals. Data collection techniques by identifying, collecting, recording, verifying, and validating data sources. Data analysis using thematic techniques. The results showed that M. Quraish Shihab emphasized the prohibition of damaging the environment and the importance of maintaining the balance of nature by combining various aspects and combining analytical methods and adobi-hijtima'i and lughawi patterns proportionally so that the interpretation was comprehensive. Analysis of Character Education Caring for the Environment contained in responsibility, avoiding damage, applies, fair, affection, and avoiding waste, which supports knowledge, feelings, and moral actions. The relevance of character education care about the environment is very relevant to the context of education and contemporary environment issues given the contemporary environment crisis and the need to increase awareness through character education based on religious values.